1986
DOI: 10.1530/acta.0.1120263
|View full text |Cite
|
Sign up to set email alerts
|

Glucose tolerance in early pregnancy

Abstract: Abstract. The effect of pregnancy on oral glucose tolerance (50 g of glucose) and plasma insulin and glucagon responses to oral glucose was studied in weeks 10 and 32 of pregnancy and again 1 year post partum in 12 normal women. Already in week 10, fasting plasma glucose was decreased and the glucose-induced insulin secretion increased as compared with post partum. However, glucose tolerance was not affected at this time. In week 32, glucose tolerance had deteriorated, although the levels of both fasting and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…As previously reported from our laboratory, this can be explained by the effect of glucose loss to the feto-placental unit or the 'feto-placental glucose steal phenomenon' [4]. The previously reported finding that fasting hypoglycaemia also occurs early in pregnancy [5,31], at which time a significant feto-placental glucose steal is not operative, suggests that other influences (most probably hormonal) are also involved in the lowering of the glucose homeostasis set point. Interestingly, beta-cell hyperresponsiveness develops early in pregnancy [31,32] and this is associated with enhanced glucose assimilation at that stage [2].…”
supporting
confidence: 63%
See 1 more Smart Citation
“…As previously reported from our laboratory, this can be explained by the effect of glucose loss to the feto-placental unit or the 'feto-placental glucose steal phenomenon' [4]. The previously reported finding that fasting hypoglycaemia also occurs early in pregnancy [5,31], at which time a significant feto-placental glucose steal is not operative, suggests that other influences (most probably hormonal) are also involved in the lowering of the glucose homeostasis set point. Interestingly, beta-cell hyperresponsiveness develops early in pregnancy [31,32] and this is associated with enhanced glucose assimilation at that stage [2].…”
supporting
confidence: 63%
“…The previously reported finding that fasting hypoglycaemia also occurs early in pregnancy [5,31], at which time a significant feto-placental glucose steal is not operative, suggests that other influences (most probably hormonal) are also involved in the lowering of the glucose homeostasis set point. Interestingly, beta-cell hyperresponsiveness develops early in pregnancy [31,32] and this is associated with enhanced glucose assimilation at that stage [2]. Ogata et al [5], on the basis of basal findings, also concluded that there was lowering of the plasma glucose set point in pregnancy.…”
mentioning
confidence: 95%
“…Maternal hyperphagia [23] increases the availability of substrates, which together with higher insulin levels and even enhanced insulin sensitivity [24][25][26] during early pregnancy, results in enhanced lipogenesis [27]. A second factor that appears to contribute to the accumulation of fat depots during early pregnancy is the increasd activity of adipose tissue lipoprotein lipase (LPL) [28,29].…”
Section: Maternal Lipid Metabolism In Pregnancymentioning
confidence: 99%
“…The lower lipolytic activity together with the augmented capacity of the tissues for the synthesis of glycerol-3-phosphate for uses in TG synthesis from both glucose and intracellular released glycerol results in net intracellular accumulations of TGs. Since all these pathways are stimulated by insulin, it is proposed that the enhanced insulin responsiveness [37] in the presence of an augmented response of the pancreatic β-cells to the insulinotropic stimulus of glucose that has been found in early pregnant women [38] would be the principal driving forces for the net fat depot accumulation at this stage of pregnancy. These ultimately lead to maternal fat accumulations in the anabolic phase of gestation.…”
Section: The Importance Of Lipid and Lipoprotein Ratios In Interpretementioning
confidence: 99%
“…Placental growth hormone, human placental lactogen, leptin, and tumour necrosis factor-α(TNF-α) are placental hormones that induce insulin resistance. The presence of high plasma levels of placental hormones, known to have lipolytic effects, human placental lipase (HPL), an augmented production of catecholamine secondary to maternal hypoglycemia [38], and the insulin-resistant condition present at this stage [39,40], appear to be responsible for the net breakdown of maternal fat depots, consistently causing increments of plasma nonesterified fatty acids(NEFA) and glycerol levels during the 3 rd trimester of gestation. The main destination of these lipolytic products released from maternal adipose tissue is the maternal liver.…”
Section: The Importance Of Lipid and Lipoprotein Ratios In Interpretementioning
confidence: 99%